2022
DOI: 10.3389/fmolb.2021.800679
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutation Profiles Revealed by Next Generation Sequencing (NGS) in 39 Chinese Hepatocellular Carcinoma Patients

Abstract: The features and significance of somatic mutation profiles in hepatocellular carcinoma (HCC) have not been completely elucidated to date. In this study, 39 tumor specimens from HCC patients were collected for gene variation analysis by next-generation sequencing (NGS), and a correlation analysis between mutated genes and clinical characteristics was also conducted. The results were compared with genome data from cBioPortal database. Our study found that T > G/A > C transversions (Tv) and C &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A study analyzing the somatic mutation profile in Chinese patients with hepatocellular carcinoma by NGS also revealed the mutation profile of mucin genes, including MUC4, MUC17, MUC12, and MUC16. MUC17 was further found to have more co-mutations with TP53 [34]. A previous study using the same gene panel showed significantly higher mutation rates in MUC17 in the ESCC cohort compared to data from The Cancer Genome Atlas (79.5% vs. 5.7%) [18].…”
Section: Discussionmentioning
confidence: 70%
“…A study analyzing the somatic mutation profile in Chinese patients with hepatocellular carcinoma by NGS also revealed the mutation profile of mucin genes, including MUC4, MUC17, MUC12, and MUC16. MUC17 was further found to have more co-mutations with TP53 [34]. A previous study using the same gene panel showed significantly higher mutation rates in MUC17 in the ESCC cohort compared to data from The Cancer Genome Atlas (79.5% vs. 5.7%) [18].…”
Section: Discussionmentioning
confidence: 70%
“…AHNAK2 has rarely been studied in HCC. A study collected 39 specimens of HCC patients from China, 22 of which were subjected to whole exome sequencing, and revealed a high mutation rate in AHNAK2 (22.7%, 5/22), although the high mutation rate in AHNAK2 was not explored in more detail ( 81 ).…”
Section: Relationship Between Ahnak Family and Tumor Developmentmentioning
confidence: 99%